Angel in “the Cartesian theatre” – Aquinas and the mind-body problem - Tomasz Stępień (Warszawskie Studia Teologiczne)
One of the solutions of the mind-body problem, which returns to the philosophical discussion on consciousness is the “soul hyphotesis”. Existence of the soul can clear the “explanatory gap”, but it brings yet another problems in explanation of how consciousness works. The magiority of those issues exist because of very specific understanding of the mind-body relations in Cartesian way as two separated substances. Some of the schoars propose to overlap the Cartesian approach by returning to the philosophy of St Thomas Aquinas. This article shows that in the writings of Aquinas we can find exact analogy of the Cartesian view of the body-soul relations in the description of how immaterial angel assums the body. For Aquinas angel exist and acts in assumed human body in the very same way as Descartes describes the soul acting in human body, and angel’s mode of perception is similar to what is usually called as “the Cartesian theatre”. For Aquinas angel in assumed body cannot perfom any human action, it only pretends to perform it, because it operates bodily organs as the form, which is not united with this specific body. St Thomas explanation of the relation of body and soul in human being relies on the claim of unity of body and soul, which together are one substance. Such approach was even called biological, because of the stress on the role which body plays in human actions. Therefore Aquinas proposition could be perceived the way of overcoming the dualism and removing some of the dilemas which are linked with “soul hypothesis” understood in traditional way.